Pengaruh Kompensasi dan Beban Kerja terhadap Loyalitas Karyawan di Hotel Tanjung Surabaya - Hilda Yunita Wono; Ismojo Herdono; Jefferson Ronaldo (Neolectura, 2021)
The increasing number of tourist visits made in Indonesia, of course, must be balanced with the increase in hotels in Indonesia. One of them is in Surabaya, in that city many hotels, from non-star to five-star, are built in the city. This study aims to determine whether workload and compensation affect employee loyalty at Hotel Tanjung Surabaya. The data collection technique used is saturated sampling, where samples are taken from the entire population. The sample used in the study was 30 respondents. This research uses quantitative methods, data collection methods use a few interviews and questionnaires using a Likert scale. Data were analyzed using software called Statistical Package for the Social Sciences (SPSS). The results of this study prove that compensation and workload have a significant positive effect on employee loyalty.